2016
DOI: 10.1634/theoncologist.2015-0298
|View full text |Cite
|
Sign up to set email alerts
|

The European Medicines Agency Review of Decitabine (Dacogen) for the Treatment of Adult Patients With Acute Myeloid Leukemia: Summary of the Scientific Assessment of the Committee for Medicinal Products for Human Use

Abstract: On September 20, 2012, a marketing authorization valid throughout the European Union (EU) was issued for decitabine for the treatment of adult patients aged 65 years and older with newly diagnosed de novo or secondary acute myeloid leukemia (AML) who are not candidates for standard induction chemotherapy. Decitabine is a pyrimidine analog incorporated into DNA, where it irreversibly inhibits DNA methyltransferases through covalent adduct formation with the enzyme.The use of decitabine was studied in an open-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Contrary to EMA, FDA has not approved decitabine for AML treatment due to its lack of efficacy (the drug was only approved for myelodysplasic syndrome). 6 This limitation may be due to its short half-life. Incorporation of decitabine in an Figure 6 cell viability following exposure of hel (A) and hl-60 (B) cells to various concentrations of free-decitabine, blank ThP-T80-lNcs, or decitabine-loaded ThP-T80-lNcs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to EMA, FDA has not approved decitabine for AML treatment due to its lack of efficacy (the drug was only approved for myelodysplasic syndrome). 6 This limitation may be due to its short half-life. Incorporation of decitabine in an Figure 6 cell viability following exposure of hel (A) and hl-60 (B) cells to various concentrations of free-decitabine, blank ThP-T80-lNcs, or decitabine-loaded ThP-T80-lNcs.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of median survival (2.7 months) is modest, but was considered to be meaningful by the EMA in the context of AML in older patients without alternative treatment. 6 A Phase II clinical trial (NCT01786343) is ongoing with modified dosing schedules to increase the cytotoxic activity of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Decitabine is approved by the European Medicines Agency, but not by the US FDA, for the treatment of adult patients with AML [41]. In this respect, decitabine is active in inducing complete remissions in patients with AML, but has a modest effect on overall survival, highlighting the need to improve the outcome of decitabine treatment [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the distal promoter region of the TERT gene and identified the TERT-DMR, which provides additional information for the human TERT gene. Of note, the demethylating reagent 5-aza-dC (also known as decitabine) has been used clinically for treating acute myeloid leukemia (AML) in patients whose malignant cells express TERT gene [34]. In addition, treatment with decitabine has been reported to suppress expression and inhibit malignant cell proliferation [35,36].…”
Section: Role Of Hypermethylation Of the Tert-dmr In Regulating Tert mentioning
confidence: 99%